Resolving Inheritance Conflicts and Their Legal Repercussions in Aceh: A Sociological and Anthropological Look at Peace Initiatives Using Customary Courts - M. Amin, Sayuthi; Hakim, Lukman; Hasballah, Khairuddin; Khairani, Khairani; Mustaqiem, Riza Afrian (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The division of inheritance is a legal matter that intersects significantly with local customs and cultural practices. Within the field of legal studies, dispute resolution is generally categorized into two pathways: litigation (formal legal processes) and non-litigation (customary deliberation). Non-litigation methods include Alternative Dispute Resolution (ADR) and customary courts, the latter being a distinctive feature of Aceh's legal landscape, recognized as a special domain of customary law by the Indonesian government. Each approach to resolving inheritance disputes, whether through formal or customary channels, presents its own advantages and drawbacks. This article examines the resolution of inheritance disputes and the legal consequences arising from the application of customary justice mechanisms in Aceh. The research adopts an empirical legal methodology, incorporating sociological and anthropological perspectives. Fieldwork was conducted in Aceh Besar, Central Aceh, and Aceh Tamiang districts, utilizing interviews and literature reviews for data collection. The findings reveal that inheritance division in local tradition follows the concept of trok uroe, with distribution being the responsibility of the heirs. Inheritance disputes in Aceh are predominantly resolved through non-litigation avenues, specifically through customary institutions operating within the gampong and mukim customary courts. The resulting legal implications are primarily non-litigation impacts, including both primary and secondary social effects, though these are not overwhelmingly dominant. Litigation-based legal consequences, while present, are minimal in influence. From a sociological and anthropological standpoint, the preference for non-litigation approaches contributes positively to social cohesion and cultural preservation within the Acehnese society.